Resiliensi Mahasiswa Pengemudi Ojek Online (Maxim) Di Lingkungan Pendidikan Universitas Sebelas Maret Surakarta - Gariska, Patria Dhony; Septina Galih Pudyastuti; Danang Purwanto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
The essence of a student is to prepare his or her future with adequate academic quality and ability. However, due to the different backgrounds of students, it affects the lecture study process. One of them is a student who studies while being a maxim driver. This research aims to: 1) find out the motivation of FKIP UNS students to study while becoming maxim drivers, and 2) find out the resilience of FKIP UNS students who study while becoming maxim drivers. The method used in this research is descriptive qualitative. Data collection techniques were carried out through semi-structured in-depth interviews with 3 active FKIP UNS students. Data analysis technique from Miles & Huberman. By adapting the resilience theory from Connor & Davidson which explains the aspects of resilience formation, namely: 1) Trust in instincts, tolerance of negative influences, strengthening oneself from stress, 2) Personal competence, tenacity, and high standards, 3) Self-control, and 4) Spiritual influrnces. The result is that student motivation to study while working as a maxim driver is influenced by background, and the quality of student resilience is influenced by 4 interrelated aspects, in the form of self-confidence, personal competence, self-control, and spiritual aspects.